Subject Review on Different Routing Algorithms for WSN - Doaa Mohsin Abd Ali; Donia Fadil Chalob; Ameer Badr Khudhair (Genius Journals, 2022)
In recent years, WSN technologies have developed and the need to use smart methods that reduce energy consumption to improve the performance of wireless networks has increased as an effective approach to artificial intelligence instead of other known energy-saving techniques in investing energy for different WSN networks. This review article was submitted for to answer two important questions related to WSN wireless sensor networks. The first question: Do we need to use smart methods that optimize energy consumption to improve the performance of wireless networks as an effective approach to artificial intelligence instead of other known energy-saving techniques in investing energy for different WSN networks? The second question is, have any recent AI techniques been used to reduce the power of Bluetooth WSNs in the literature? In fact, to answer these two important questions, one should refer to the literature and related works related to this field of research. And from the point of view of knowledge, the second question is the most important to answer first.
Keywords: Wireless Sensor Networks; Artificial Inteliegence Algorithms; Energy Saving; Remote Servers